Ontology-based Approach: A Smartphone Knowledge Representation - Indrayasa, I Wayan Gede; Pramartha, Cokorda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
The development of technology in the modern era is currently increasing very rapidly so that it can make human work easier. One of the technologies that are often used by the community to meet the needs of life is a smartphone. The rapid development of smartphones has made people's purchasing power higher with existing criteria, ranging from brands, prices to features that potential buyers must consider in buying a smartphone. The lack of public knowledge also makes people confused about choosing a smartphone product because of the many smartphone brands on the market. Ontology can be a solution to explicitly describe information about smartphones. The construction of an ontology model is carried out using the methodology methodology. The ontology that was built has 7 classes, 12 subclasses, 9 object properties, 2 data properties, and 92 instances. The ontology built using SPARQL with several search criteria on this ontology can produce the output that the user wants and can represent knowledge from a set of concepts in the knowledge domain, in this case the smartphone and its relationship between these concepts.